Daya Tarik Taman Widya Puraya Universitas Diponegoro Sebagai Taman Aktif Oleh Masyarakat Umum - Aditya Mula Kurniawan; Hadi Wahyono (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Widya Puraya Park is a public space that owned by Universitas Diponegoro. Widya Puraya Park used as an open space for all ceremonial activity of Diponegoro University. Widya Puraya park is located in front of Widya Puraya building in Diponegoro University. But, as time goes by, Widya Puraya Park used also by the people who lived around Diponegoro University. The Park now also used as a recreation park by the people. Widya Puraya Park has something that could attract people to come. Researcher feel the need for identification about the attraction of Widya Puraya Park measured by visitor’s perceptions, also the correlation between the attraction and quality of Widya Puraya Park. The purpose of this research is to measure the attraction of Widya Puraya Park. The approach of this research is quantitative approach with crosstab analysis. This research uses quantitative descriptive analysis technique. The result of this research shows that the variables that have correlation with the quality of the park is visual attraction with visual quality of the park, amenities attraction with visual quality, amenities attraction with amenities quality and activity attraction. Based on crosstab analysis, the quality of Widya Puraya Park that attract people to come are visual quality and amenities quality. In other words, the society who lived around Diponegoro University come to Widya Puraya Park because of interested in the visual quality and amenities of Widya Puraya Park.